2014
DOI: 10.1111/bjd.13374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological profiles of 25 patients with pemphigoid gestationis

Abstract: IB and ELISA of the NC16a domain of BP180 were shown to be sensitive and diagnostic methods in PG. Patients with PG rarely reacted with BP230, suggesting a different pathogenesis between PG and bullous pemphigoid. Multigravidae developed PG skin lesions significantly earlier in pregnancy than primigravidae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
3
34
1
3
Order By: Relevance
“…The intraepidermal blisters seemed to be the result of severe spongiosis or may be attributed to the age of the lesion (old lesions can be partially re-epithelialized). These findings are similar to those from the study by Tani et al (2015) who observed subepidermal bulla in 16 patients (67%), spongiosis in eight patients (33%), apparent intraepidermal bulla in four patients (17%), papillary dermal edema in three patients (13%), and liquefaction degeneration in two patients (8%). The researchers believe that these results are different from those obtained in BP and may be explained by the fact that anti-BP180 antibodies in PG tend to induce inflammation rather than blisters and epidermis was preferentially affected in patients with PG.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The intraepidermal blisters seemed to be the result of severe spongiosis or may be attributed to the age of the lesion (old lesions can be partially re-epithelialized). These findings are similar to those from the study by Tani et al (2015) who observed subepidermal bulla in 16 patients (67%), spongiosis in eight patients (33%), apparent intraepidermal bulla in four patients (17%), papillary dermal edema in three patients (13%), and liquefaction degeneration in two patients (8%). The researchers believe that these results are different from those obtained in BP and may be explained by the fact that anti-BP180 antibodies in PG tend to induce inflammation rather than blisters and epidermis was preferentially affected in patients with PG.…”
Section: Discussionsupporting
confidence: 90%
“…The detection of C 3 reactivity to BMZ by direct and complement-added indirect immunofluorescence testing is the golden standard laboratory study for diagnoses of PG (Sitaru et al, 2004). Recently, immunoblotting and enzyme-linked immunosorbent assays of the NC16a domain of BP180 have shown to be sensitive diagnostic tools for PG (Tani et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG auto-antibodies directed against the NC16A domain of BP180 can be found in 90% of patients with PG and, in some cases, remain positive after delivery (4)(5)(6)(7)(8). Autoantibodies against a second hemidesmosomal protein, BP230, have been reported in up to 16% of PG sera (9), but the frequency of anti-BP230 auto-antibodies in healthy controls was not determined in this Japanese study. Detection of serum anti-BP180 NC16A IgG autoantibodies by enzyme-linked immunoassay (ELISA) is the most convenient diagnostic method for PG.…”
contrasting
confidence: 56%
“…Fetal prognosis is good, but early onset in 2nd trimester and blister formation are risk factors for prematurity and low birth weight. Rarely, the newborn may be aff ected by very transitory blisters [5].…”
Section: Discussionmentioning
confidence: 99%